Educational migration from the countries of the Commonwealth of Independent States to the Russian Federation - Kajumovna Karimova, Luiza (2021)
Nowadays educational migration is still one of the most relevant topics for Russian and foreign scientists and understudied topic at the same time. Despite the many published sources including quantitative and qualitative aspects of the process, the set of topics under consideration is quite limited (adaptation of foreign students, brain drain, demographical characteristics of migrants, etc.). The article using scientific principles of systematicity and general scientific methods (analysis, synthesis, induction, deduction, comparison, classification, etc.) considers the dynamics of the changes in the amount of foreign students from the countries of the Commonwealth of Independent States to the Russian Federation (including which countries they are from), correlation of the process with forming-up Common Education Space in Russia and CIS. The study conducted led to the conclusion that the actions by government agencies of the Russian Federation, higher education institutions and scientific organizations allowed stopping the negative process of foreign students drain, which took place in 1990-s, promoting and increasing the educational migrant influx from the countries of the Commonwealth of Independent States from 2000 to 2007. Among the leaders in the number of students studying at Russian universities, in early 1990-s there were Kazakhstan, Ukraine and Belorussia and in 2017 there were Kazakhstan, Turkmenistan and Uzbekistan.